Burst‐swimming performance predicts the outcome of cannibalistic interactions in green poison frog larvae (Dendrobates auratus). Issue 9 (6th August 2013) - Wilcox, Sean C.; Lappin, A. Kristopher
ABSTRACT Whole‐animal performance (e.g., swimming speed, bite force) functions as a fundamental link between organism and environment and, as such, performance characteristics are important in determining the outcomes of agonistic interactions, both interspecific and intraspecific. Cannibalism is an intraspecific agonistic interaction for which winners may be expected to exhibit superior performance in characteristics relevant to cannibalistic behavior. The larvae of the Green Poison Frog (Dendrobates auratus) exhibit cannibalistic behavior in which "fast‐starts" (i.e., high velocity and acceleration from a resting position) are used in attempts to bite and avoid being bitten by conspecifics. We tested the hypothesis that superior fast‐start swimming performance is positively associated with winning cannibalistic interactions between similarly sized individuals. Fast‐starts by larvae were imaged with a high‐speed camera, and pairs of size‐matched individuals then underwent interaction trials to determine whether swimming performance is associated with winning a cannibalistic interaction. Linear acceleration of the snout tip, approximating the position of the mouthparts used to attack an opponent, was significantly greater in winners than losers. At the estimated center of mass, generally representing a target for an attacking opponent, linear velocity and acceleration were significantly greater in winners than losers. Understanding the role of performance in intraspecific interactions can help elucidate how they contribute to population dynamics, and thus how such interactions ultimately drive morphological and behavioral evolution. J. Exp. Zool. 319A: 495–504, 2013. © 2013 Wiley Periodicals, Inc.